Hermeneutika al-Qurâ€™an â€œMazhab Yogyaâ€ (Telaah atas Teori Maâ€™na>-Cum-Maghza> dalam Penafsiran A l-Qurâ€™an - Setiawan, Asep (UIN Sunan Kalijaga Yogyakarta, 2016)
This article tries to discuss the discourse of the application of hermeneutics in Qur’anic studies, as seen in the theory of ma’na>-cum-maghza> offered by Muslim scholars in Yogyakarta. It argues that even though the effort of those who initiate the incorporation of hermeneutics to Qur’anic studies needs to be appreciated, its use as an approach to interpret the Qur’an is problematic. Taking into account its assumptions and implications, hermeneutics is not appropriate to be applied in the study of the Qur’an as it leads to confusion and doubt. The main issue is that hermeneutics departs from skepticism and relativism, equates the Qur’an with other texts, and produces uncertainty in meanings and relative-tentative interpretations.Keywords: hermeneutics, ma’na>-cum-maghza>, interpretation, Qur’anic studies.